Facile Access to 3-Unsubstituted Tetrahydroisoquinolonic Acids via the Castagnoli–Cushman Reaction - Guranova, Natalia; Dar’in, Dmitry; Krasavin, Mikhail (Synthesis, 2018)
Hitherto undescribed 3-unsubstituted tetrahydroisoquinolonic acids (isolated as their respective methyl esters) were accessed for the first time by the uncatalyzed, thermally promoted Castagnoli–Cushman reaction (CCR) of homophthalic anhydride (HPA) and a series of 1,3,5-triazinanes. The moderate yields observed in some cases are most likely associated with a persistent impurity also formed in these reactions. The new scaffold is expected to find novel medicinal utility (compared to the traditional CCR adducts) because it lacks a substituent at the 3-position.
Keywords: tetrahydroisoquinolonic acids; Castagnoli–Cushman reaction; 1,3,5-triazinanes; homophthalic anhydride